2022
DOI: 10.3390/toxics10080428
|View full text |Cite
|
Sign up to set email alerts
|

Boron Compounds Exhibit Protective Effects against Aluminum-Induced Neurotoxicity and Genotoxicity: In Vitro and In Vivo Study

Abstract: Genetic, neuropathological and biochemical investigations have revealed meaningful relationships between aluminum (Al) exposure and neurotoxic and hematotoxic damage. Hence, intensive efforts are being made to minimize the harmful effects of Al. Moreover, boron compounds are used in a broad mix of industries, from cosmetics and pharmaceuticals to agriculture. They affect critical biological functions in cellular events and enzymatic reactions, as well as endocrinal and mineral metabolisms. There are limited do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 128 publications
0
17
0
2
Order By: Relevance
“…Boron compounds have extensive chemical applications, and boron itself serves as a fundamental micronutrient utilized by both plants and humans, but there are limited data that suggest that boron compounds, particularly organoboranes, exhibit cytoprotective effects. In light of the key role of (phospho)­lipid peroxidation in ferroptosis, we sought to determine whether the ArB­(DAN) and ArB­(Me 2 -DAN) derivatives could serve as scaffolds for new antiferroptotic agents. Although lipophilic RTAs comprise the most potent inhibitors to date, they almost exclusively inhibit lipid peroxidation and subsequent cell death by H-atom transfer. , Examples include ferrostatin-1, liproxstatin-1, phenoxazine, α-tocopherol, and hydropersulfides. ,, Only CuATSM and related metal bis­(thiosemicarbazones) have been shown to suppress ferroptosis by a non-HAT RTA mechanism .…”
Section: Resultsmentioning
confidence: 99%
“…Boron compounds have extensive chemical applications, and boron itself serves as a fundamental micronutrient utilized by both plants and humans, but there are limited data that suggest that boron compounds, particularly organoboranes, exhibit cytoprotective effects. In light of the key role of (phospho)­lipid peroxidation in ferroptosis, we sought to determine whether the ArB­(DAN) and ArB­(Me 2 -DAN) derivatives could serve as scaffolds for new antiferroptotic agents. Although lipophilic RTAs comprise the most potent inhibitors to date, they almost exclusively inhibit lipid peroxidation and subsequent cell death by H-atom transfer. , Examples include ferrostatin-1, liproxstatin-1, phenoxazine, α-tocopherol, and hydropersulfides. ,, Only CuATSM and related metal bis­(thiosemicarbazones) have been shown to suppress ferroptosis by a non-HAT RTA mechanism .…”
Section: Resultsmentioning
confidence: 99%
“…Neurodegenerative disease progression has been extensively shown to be influenced by oxidative stress, inflammation, and apoptosis (Behl et al, 2021;Merelli et al, 2021;Zarneshan et al, 2022). In this regard, previous studies indicated that Al exposure can induce various neurological disorders (Aly et al, 2011;Hamdan et al, 2022;Turkez et al, 2022). Therefore, chronic exposure to Al in mouse models has frequently been used as an experimental model of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Aluminum is one of the most abundant metals found in the earth crust. It is found in many products, making humans prone to daily exposure ( Abbas et al, 2022 ; Hamdan et al, 2022 ; Turkez et al, 2022 ). The daily intake of aluminum depends up on the food type.…”
Section: Introductionmentioning
confidence: 99%
“…Boron compounds at low concentrations (<20 mg L −1 ) increased antioxidant enzyme activities in humans. 18,19 Considering boron studies and the disadvantages of present food preservatives, it has become necessary to investigate the use of boron derivatives in aquaculture processing. The study's primary purpose is to investigate the potential of boron derivative usage in biofilm coatings as a food preservative in the aquaculture industry.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that boron is a micronutrient that plays a vital role in an organism's metabolism. Boron compounds at low concentrations (<20 mg L −1 ) increased antioxidant enzyme activities in humans 18,19 . Considering boron studies and the disadvantages of present food preservatives, it has become necessary to investigate the use of boron derivatives in aquaculture processing.…”
Section: Introductionmentioning
confidence: 99%